2020
DOI: 10.1016/j.virusres.2020.198167
|View full text |Cite
|
Sign up to set email alerts
|

Rhodanine derivative LJ001 inhibits TGEV and PDCoV replication in vitro

Abstract: Highlights LJ001 have the antiviral activity against TGEV or PDCoV infection in vitro. LJ001 inhibits TGEV or PDCoV infection at the replication stages of viral life cycle. LJ001 may serve as a new candidate for treatment of swine enteric coronavirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Lithium chloride and diammonium glycyrrhizinate (DG) were reported to inhibit PDCoV replication at the early stage in LLC-PK1 cells, and DG also inhibited virus attachment to the cells [ 23 ]. Rhodanine derivative LJ001 showed antiviral activity against PDCoV infection in ST cells [ 24 ]. Besides, PDCoV was shown to be susceptible to remdesivir treatment in Huh7 cells [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lithium chloride and diammonium glycyrrhizinate (DG) were reported to inhibit PDCoV replication at the early stage in LLC-PK1 cells, and DG also inhibited virus attachment to the cells [ 23 ]. Rhodanine derivative LJ001 showed antiviral activity against PDCoV infection in ST cells [ 24 ]. Besides, PDCoV was shown to be susceptible to remdesivir treatment in Huh7 cells [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rhodanine derivative LJ001 possesses effective inhibitory ability at the replication stage of PDCoV life cycle in ST cells. It restricts the synthesis of viral RNA and protein, and reduces viral production ( 88 ). 25-hydroxycholesterol (25HC), the product of cholesterol oxidation by the enzyme CH25H, inhibits PDCoV infection by blocking PDCoV entry ( 70 ).…”
Section: Current Anti-pdcov Strategiesmentioning
confidence: 99%
“…For example, lithium chloride and diammonium glycyrrhizinate could inhibit PDCoV replication in LLC-PK cells in a dose-dependent manner ( Zhai et al, 2019 ). In addition, Zhang explored the inhibitory effect of LJ001 on PDCoV in three ways ( Zhang et al, 2020 ). He found that the antiviral effect of pretreatment was not significant, which may be because the receptor sites available for virus attachment on the cell membrane are altered after the cells are pretreated with the drug, which affects the fusion of virus and cells ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhang explored the inhibitory effect of LJ001 on PDCoV in three ways ( Zhang et al, 2020 ). He found that the antiviral effect of pretreatment was not significant, which may be because the receptor sites available for virus attachment on the cell membrane are altered after the cells are pretreated with the drug, which affects the fusion of virus and cells ( Zhang et al, 2020 ). Studies on the inhibition of viral replication by selenium have been reported, for example, HIV, Coxsackie virus, influenza virus, and PCV ( Beck et al, 1994 ; Schrauzer and Sacher, 1994 ; Nelson et al, 2001 ; Jaspers et al, 2007 ; Qian et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%